2003
DOI: 10.1038/sj.bjc.6601002
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of advanced colorectal cancer by screening using the immunochemical faecal occult blood test: a case–control study

Abstract: To evaluate colorectal cancer screening with faecal occult blood testing (FOBT) in terms of prevention of advanced cancers, we conducted a case -control study in the areas where an annual screening programme with immunochemical FOBT has been offered to all inhabitants aged 40 years or over. Cases were 357 consecutive patients in the study areas clinically diagnosed as having advanced colorectal cancer or a tumour invading the muscularis propriae or deeper, that is, T 2 -T 4 in TNM classification. Three control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 34 publications
0
35
0
1
Order By: Relevance
“…In a case control study from Japan, in which subjects over the age of 40 years were invited for yearly faecal occult blood testing using the immunochemical test, the risk of developing advanced cancer was significantly reduced among those who were screened within the past three years. 1 A screening programme with immunochemical faecal occult blood testing appears to be effective for the prevention of advanced colorectal cancer, especially rectal cancers. On the other hand, flat or depressed adenomas, which were first described in Japan, are now more widely recognised as a distinct entity.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…In a case control study from Japan, in which subjects over the age of 40 years were invited for yearly faecal occult blood testing using the immunochemical test, the risk of developing advanced cancer was significantly reduced among those who were screened within the past three years. 1 A screening programme with immunochemical faecal occult blood testing appears to be effective for the prevention of advanced colorectal cancer, especially rectal cancers. On the other hand, flat or depressed adenomas, which were first described in Japan, are now more widely recognised as a distinct entity.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…This has already been used as a population screening test and a reduction in risk of dying from colorectal cancer after screening with this test has been consistently suggested by several studies, although these were observational (Saito et al, 1995(Saito et al, , 2000Saito, 1996;Zappa et al, 1997). In our most recent study, reduction in risk of developing advanced colorectal cancer has additionally been suggested (Nakajima et al, 2003). Furthermore, it was demonstrated that sensitivity was higher for this test than for the Haemoccult test (St John et al, 1993;Allison et al, 1996;Saito and Yoshida, 1996).…”
Section: Sirmentioning
confidence: 94%
“…The article of Nakajima et al (2003) in the Journal addresses a problem of major public health importance, concluding that screening programme with immunochemical faecal occult blood test (FOBT) can be effective for prevention of advanced colorectal cancer. However, the screening method applied in their casecontrol study (i.e.…”
Section: Sirmentioning
confidence: 99%